2018
DOI: 10.1101/262634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diet Modifies Colonic Microbiota and CD4+ T Cell Repertoire to Trigger Flares in a Novel Model of Colitis Induced by IL-23

Abstract: A wealth of experimental data points to immunological and environmental factors in the pathogenesis of inflammatory bowel disease (IBD). Here we study the role of IL-23, the microbiome, and the diet in the development of colitis. To promote IL-23 expression in vivo,we generated a mouse model in which IL-23 was conditionally expressed by CX 3 CR1 + myeloid cells, upon cyclic administration of tamoxifen in a specific diet (diet 2019). IL-23 expression induced an intestinal inflammatory disease that resembled ulc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 67 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…In our previous study, we found that overexpression of IL-23 by myeloid cells does not appear to be sufficient for induction of colitis in adult mice (Chen et al, 2018). The mice we developed conditionally express IL-23 in CX3CR1-positive myeloid cells (R23FR mice).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our previous study, we found that overexpression of IL-23 by myeloid cells does not appear to be sufficient for induction of colitis in adult mice (Chen et al, 2018). The mice we developed conditionally express IL-23 in CX3CR1-positive myeloid cells (R23FR mice).…”
Section: Introductionmentioning
confidence: 97%
“…The mice we developed conditionally express IL-23 in CX3CR1-positive myeloid cells (R23FR mice). R23FR mice were generated by crossing Rosa26-lox-STOP-lox-IL23 mice with CX3CR1 CreER mice (FR mice) (Chen et al, 2018). Upon tamoxifen (TAM) treatment, R23FR mice express IL-23 in CX3CR1-positive cells but do not develop colitis when fed the standard diet used in our facility (Labdiet 5053).…”
Section: Introductionmentioning
confidence: 99%
“…To further study the biology of IL-23 in neonates we engineered mice in which expression of IL-23 was targeted constitutively to CX3CR1 + cells, which are the cells that predominantly express IL-23 in the intestine. This was accomplished by intercrossing mice containing a IL-23 cassette preceded by a floxed STOP signal in the ROSA 26 locus (R23 mice) (Chen et al, 2018), with mice containing a cre recombinase gene inserted into the CX3CR1 locus (CX3CR1-cre mice) (Yona et al, 2013). We refer to these animals as CXR23 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mice. R23 mice were described in (Chen et al, 2018). R23 mice were backcrossed into the C57BL/6 background for 11 generations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation